Trends and concerns of potentially inappropriate medication use in patients with cardiovascular diseases. Issue 10 (3rd October 2021) - Anfinogenova, Nina D.; Trubacheva, Irina A.; Popov, Sergey V.; Efimova, Elena V.; Ussov, Wladimir Y.
ABSTRACT: Introduction : The use of potentially inappropriate medications (PIM) is an alarming social risk factor in cardiovascular patients. PIM administration may result in iatrogenic disorders and adverse consequences may be attenuated by limiting PIM intake. Areas covered : The goal of this review article is to discuss the trends, risks, and concerns regarding PIM administration with focus on cardiovascular patients. To find data, we searched literature using electronic databases (Pubmed/Medline 1966–2021 and Web of Science 1975–2021). The data search terms were cardiovascular diseases, potentially inappropriate medication, potentially harmful drug–drug combination, potentially harmful drug–disease combination, drug interaction, deprescribing, and electronic health record. Expert opinion : Drugs for heart diseases are the most commonly prescribed medications in older individuals. Despite the availability of explicit and implicit PIM criteria, the incidence of PIM use in cardiovascular patients remains high ranging from 7 to 85% in different patient categories. Physician-induced disorders often occur when PIM is administered and adverse effects may be reduced by limiting PIM intake. Main strategies promising for addressing PIM use include deprescribing, implementation of systematic electronic records, pharmacist medication review, and collaboration among cardiologists, internists, geriatricians, clinical pharmacologists, pharmacists, and other healthcare professionals as basis of multidisciplinary assessment teams.